COLLABORATIF GOVERNANCE DALAM PEMBERDAYAAN INDSUTRI PANDAI BESI DI DESA MASSEPE - Sri Wirdana; Jumria Basri (Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to identify the role of parties in the blacksmith industry, detail short-term and long-term steps to support government policy and explore the role of collaborative governance in strengthening this sector. The blacksmith industry is an essential economic sector facing the challenges of globalization. This research uses qualitative methods with interviews, observation, and document analysis. Collaboration between the public, private, and local community sectors increases resource access, industrial capacity, and policy efficiency. Although still in its infancy, collaborative governance can potentially strengthen the sector. Alignment and commitment of all parties involved are essential. These findings are relevant for decision-makers, business people, and academics.